INTERACTION OF MARKETING AND LOGISTICS AT STAGES OF LIFE CYCLE OF PRODUCTS - K. Igrokova (Вестник университета, 2019)
The arguments proving necessity of interaction of marketing and logistics departments in companies that deal with fast moving products. The modern evaluation treatment connecting problems of marketing and logistics is given. The carrying out of evaluation coordination problems both logistics and marketing for the efficiency of their interaction.The marketing and logistics functions are discussed. These functions are concretized towards all problems of their coordination. Communication management efficiency with competent interactions of services of marketing and logistics is tracked.